Historical Tables 58 BC – AD 1990 - Steinberg, S.H. author. aut Link
IX, 324 p.
Keywords: This book, now in its twelfth edition, has become indispensable to every library and to every serious student of history. The twelfth edition takes the tables up to the end of 1990 and so records all the dramatic events occurring in Eastern Europe at the end of the decade. An important new feature is that an index has been provided thus enhancing this essential reference tool.